Unraveling the regulatory network of miRNA expression in Potato Y virus-infected of Nicotiana benthamiana using integrated small RNA and transcriptome sequencing - Song, Hongping; Gao, Xinwen; Song, Liyun; Jiao, Yubing; Shen, Lili; Yang, Jinguang; Li, Changquan; Shang, Jun; Wang, Hui; Zhang, Songbai; Li, Ying (Frontiers in Genetics, 2024)
Potato virus Y (PVY) disease is a global problem that causes significant damage to crop quality and yield. As traditional chemical control methods are ineffective against PVY, it is crucial to explore new control strategies. MicroRNAs (miRNAs) play a crucial role in plant and animal defense responses to biotic and abiotic stresses. These endogenous miRNAs act as a link between antiviral gene pathways and host immunity. Several miRNAs target plant immune genes and are involved in the virus infection process. In this study, we conducted small RNA sequencing and transcriptome sequencing on healthy and PVY-infected N. benthamiana tissues (roots, stems, and leaves). Through bioinformatics analysis, we predicted potential targets of differentially expressed miRNAs using the N. benthamiana reference genome and the PVY genome. We then compared the identified differentially expressed mRNAs with the predicted target genes to uncover the complex relationships between miRNAs and their targets. This study successfully constructed a miRNA-mRNA network through the joint analysis of Small RNA sequencing and transcriptome sequencing, which unveiled potential miRNA targets and identified potential binding sites of miRNAs on the PVY genome. This miRNA-mRNA regulatory network suggests the involvement of miRNAs in the virus infection process.